Attenuation of the increase of heart rate and oxygen consumption during progressive exercise in professional rugby players - Piva, T.; Raisi, A.; Myers, J.; Zerbini, V.; Menegatti, E.; Mazzoni, G.; Grazzi, G.; Mandini, S. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The response of oxygen uptake (VO2) and heart rate (HR) to continuous progressive large muscle mass exercise is not always linear. This study aimed to compare the patterns of the Speed/VO2 (S/VO2) and speed/HR (S/HR) relationships during an incremental treadmill-running test in professional rugby players. METHODS: Fourteen professional rugby athletes performed a maximal incremental treadmill-running test, following the Conconi test protocol. Speed, heart rate, and gas exchange parameters were recorded. The slope of the S/VO2 and S/HR relationships were mathematically determined. RESULTS: The S/VO2 and S/HR relationships were linear up to a submaximal speed and curvilinear thereafter. The speed of locomotion at which the slope of the S/VO2 and S/HR relationships start to attenuate (VO2att and HRatt) were coincident (12.3±1.0 and 12.4±0.9 km/h), strongly correlated and in good agreement. VO2 values at VO2att (44.9±8.7 mL/kg/min) were significantly correlated with VO2 values at the ventilatory threshold (43.3±6.0 mL/kg/min) (R2=0.83, P=0.001) and in good agreement. The running speed/VO2 ratio (delta_S/delta_VO2) up to VO2att was significantly lower than that beyond VO2att (2.98±1.1 vs. 5.16±2.31); P<0,001). CONCLUSIONS: The speed/oxygen uptake and S/HR relationships during progressive exercise start to attenuate at a coincident exercise intensity, and at oxygen uptake values strongly correlated with the ventilatory threshold. These findings further support the usefulness of the attenuation of the S/HR relationship as a practical tool for exercise testing and training purposes in professional rugby players.